Characterizing the complexity of Australian marsupial insulin-like growth factor 1 genes. (15th May 2019) - Rotwein, Peter
Abstract: Insulin-like growth factor 1 (IGF1) actions are essential for somatic growth and tissue repair. IGF1 gene regulation is controlled by many inputs, with growth hormone playing a major role. In most mammals, the 6-exon IGF1 / Igf1 gene produces multiple transcripts via independent activity of its promoters plus alternative RNA splicing and differential polyadenylation. Here, by analyzing public genomic and RNA-sequencing repositories, I have characterized three Australian marsupial IGF1 genes. Koala, Tasmanian devil, and wallaby IGF1 are more complicated than other mammals, as they contain up to 11 exons, and encode multiple mRNAs and predicted protein precursors, including potentially novel isoforms. Moreover, just two of multiple growth hormone-stimulated transcriptional enhancers found in other IGF1 / Igf1 loci are detected in these species. These observations define Australian marsupial IGF1 genes and demonstrate that comprehensive interrogation of genomic and RNA-sequencing resources is an effective strategy for characterizing genes and gene expression in otherwise experimentally intractable organisms. Highlights: Australian marsupial IGF1 genes are more complicated than IGF1 / Igf1 genes from other mammals. Australian marsupial IGF1 genes encode unique exons that predict novel transcripts and IGF1 protein precursors. Australian marsupial IGF1 genes retain the two-promoter structure of other mammalian IGF1 / Igf1 genes. Australian marsupial IGF1 loci contain only two of the GH-activated transcriptional enhancers found in other mammals. Public genomic resources contain the raw data for understanding genes and their evolution in different organisms.